Predisposition to spina bifida: Search for a relation to maternal gastric acid secretion. - Stanway, P A (1977)
The peak acid output of the stomach in a group of 71 mothers of spina bifida children and in 71 matched controls was estimated indirectly by the serum level of group I pepsinogens. The mean levels did not differ significantly, suggesting that the conjectured teratogen is not specially acid-labile. The variance was significantly higher in index subjects than in controls, but the interpretation of this finding is not clear.